Area deprivation, individual socioeconomic status and low vision in the EPIC-Norfolk Eye Study. Issue 3 (31st October 2013) - Yip, Jennifer L Y; Luben, Robert; Hayat, Shabina; Khawaja, Anthony P; Broadway, David C; Wareham, Nick; Khaw, K T; Foster, Paul J
Abstract : Background: Poor vision is associated with lower socioeconomic status, but less is known about its relationship to area deprivation. Methods: The European Prospective Investigation into Cancer and Nutrition study Norfolk Eye Study was a cross-sectional study of 8563 participants with completed eye examinations. Logarithm of the minimum angle of resolution (logMAR) visual acuity (VA) was measured using standard protocols and low vision (LV) was defined as Snellen equivalent (VA) ≤6/12 in the better eye. Uncorrected refractive error (URE) was defined as improvement of VA by 2 logarithm of the minimum angle of resolution lines with pinhole. The lowest 5% of index of multiple deprivation rank was used to define the most deprived areas. The index of multiple deprivation is a composite measure using routine data from seven domains of deprivation to identify the most disadvantaged areas in England. Logistic regression was used to examine univariable and multivariable associations with LV. Results: Ninety-six participants with missing data were excluded, leaving 8467 for analysis (98.9%). The mean age of the study group was 68.7 years (SD=8.1, range=48–92), with 55.1% women. LV was present in 263 participants (3.1%, 95% CI 2.7 to 3.5%). LV was associated with deprivation after adjusting for age, sex, education, social class and cataract surgery (OR=1.7, 95% CI 1.1 to 2.6, p=0.03), but this effect was mitigated by additionally adjusting for URE (OR=1.5, 95% CI 1.0 to 2.4, p=0.09). Conclusions: People with LV are more likely to live in the most deprived areas; this association was independent of socioeconomic status and partly mediated by URE. Targeting URE in deprived areas may reduce health inequalities associated with LV.